Performance of Artificial Compared to Natural Coarse Aggregates as Road Pavement Materials - Agus Winardi; I Dewa Made Alit Karyawan; Buan Anshari (Postgraduate, University of Mataram, 2022)
Aggregates are the main material for road pavement made of natural stone. The availability of this natural stone will decrease because the stone is a non-renewable resource. The use of artificial aggregates can be an alternative to natural aggregates. The promotion of the use of waste as an artificial aggregates is starting to develop, especially with fly ash. Aggregates road materials must be tested to determine their characteristics by methods according to applicable standards. In this study, it can be seen that the aggregates of all quarries can be used as pavement materials, but the aggregates of the KB quarry show a poor flakiness index value. The test results of geopolymer-made aggregates made from fly ash showed that the abrasion and absorption values were not good. However, in general, it has good characteristics as road materials, so further research is needed to obtain geopolymer-made aggregates that meet the abrasion and absorption requirements for use as road materials.